Influence of chemical and mineral admixtures on shrinkage and creep of prepacked aggregate concrete - Hossein, Aslani (2013)
Prepacked aggregate concrete is a special kind of concrete which is produced by first placing the coarse aggregates inside the molds followed by injection of grout from underneath using pump or gravity method. The grout consists of sand, cement and water plus chemical and mineral admixtures. Two separate stages are included in this study: The first stage consists of manufacturing of grouts with superplastizer as chemical admixture and palm oil fuel ash as mineral admixture. Tests were conducted on grouts to examine bleeding, density, compressive strength, consistency, volume change properties. In the second stage, prepacked aggregate concrete samples were made following grouting by two methods: pump and gravity. Once the specimens were made, shrinkage and creep tests were performed following ASTM C512/C512 M-10. It has been found that the shrinkage and creep of prepacked aggregate concrete was lower than that of normal concrete in both gravity and pump specimens using chemical and mineral admixtures